Pengaruh Motivasi Kerja dan Kompensasi Terhadap Produktivitas Karyawan PT. Petrokimia Gresik - Kervin Kervin; Robin Robin; Vendy Vendy (eCo-Buss, 2023)
Businesses are looking for the most productive organization or human resources possible. Organizational effectiveness in achieving its goals will be directly influenced by the availability of competent and optimal personnel. The workforce of an organization becomes one of the elements to measure productivity as a consequence of its inefficiency and ineffectiveness. Businesses that invest in their employees through competitive pay and benefits attract and retain the best talent, which in turn benefits the bottom line, incentives for greater productivity, and also stimulates the ability of its staff to produce the best results for the business. It is important to handle compensation well because it will help the organization in achieving its goals. A person's mind and character must be trained or shaped if they want to behave properly and according to their wishes. Punishment and incentive are not the same thing. This study's goal is to identify how compensation and motivation affect PT. Petrokimia Gresik employees' productivity. Probability-free sampling combined with statistical testing is the sampling methodology used in this study. A total of 155 respondents from PT. Petrokimia Gresik made up the sample for this study. While the remaining 35,2% have an impact on other factors that were left out of this research. The analysis in this research used SPSS 25 and multiple linear regression. The findings show that motivation and compensation can provide a significant effect on employee productivity. The coefficient determination findings of 0,648 or 64,8% show that employee productivity at PT. Petrokimia Gresik is strongly influenced by motivation and compensation. Consequently, need more research that controls for other potential influences on worker output.